The winter we danced: voices from the past, the future, and the Idle No More movement - Kino-nda-niimi Collective (ARP Books, 2014)
"The Winter We Danced is a vivid collection of writing, poetry, lyrics, art and images from the many diverse voices that make up the past, present, and future of the Idle No More movement. Calling for pathways into healthy, just, equitable and sustainable communities while drawing on a wide-ranging body of narratives, journalism, editorials and creative pieces, this collection consolidates some of the most powerful, creative and insightful moments from the winter we danced and gestures towards next steps in an on-going movement for justice and Indigenous self-determination"
Section: 439 pages : illustrations (certaines en couleur) ; 22 cm
Keywords: 2000 à aujourd'hui; 2010-2019; DIG; amériques; approches et analyses; arts; canada; care; cours; créativité; discipline; féminisme autochtone; images; justice sociale; militance; musique; pol4105; poésie; premier cycle; périodes historiques; régions géographiques; santé; thématiques; études littéraires

Le vertige des insectes: roman - Veilleux, Maude (Les éditions du Septentrion, 2014)
« Le décès de sa grand-mère et le départ de son amoureuse pour le Yukon replongent Mathilde au coeur de souvenirs douloureux liés à la mort. Dans l'enceinte de son appartement, elle s'enlise lentement dans la complexité d'un quotidien aux contours sombres. Roman d'atmosphère, Le Vertige des insectes nous fait pénétrer dans un univers où illusion et divagation se collent au corps telle une seconde peau. »– Résumé de l'éditeur.
Section: 178 pages ; 20 cm.
Keywords: 2000 à aujourd'hui; 2010-2019; LGBTQIA2+; amériques; approches et analyses; arts; canada; cours; discipline; identités LGBTQIA2+; lesbianisme; lit3495; littérature; premier cycle; périodes historiques; québec; régions géographiques; thématiques; yukon; écriture des femmes*; études littéraires